This England. (New Statesman, 2020)
James Ruffell, who lives in the village of Sonning with his partner Caroline Jobbins, has set up a webcam in his front window which automatically starts recording when someone walks by. He has put up official-looking signs which tell pedestrians: "You have now entered the jurisdiction of the Ministry of Silly Walks. Westmorland Gazette (Terry Hanstock) Five-star farce TripAdvisor announced that it had temporarily suspended publishing reviews about Barnard Castle after the tourism website was flooded with fake posts from people pretending to be Dominic Cummings.